Promoting critical cultural awareness in ESL classes through rock and roll music content based workshops (2018)
ABSTRACT: This paper presents an action research study based on the implementation of a content based workshop with rock and roll to develop motivation and a critical cultural awareness in ESL teenage students from the private institution Colegio Antares. The data was collected with two surveys to students, class observations and teacher´s diary. The steps suggested by Robinson, (2011) Rock and Roll English Teaching Content-Based Cultural Workshops and language learning. The recommended structure of the workshops is: 1. The beginning: Roots and influences 2. The middle: Decades of change 3. The end: Rock and social distortion in the United States.where they develop a critical thinking about a specific culture, in our case The United States and England.